Corporate Social Responsibility Comparison of Small-Medium Enterprises in Finland and Pakistan: - Khan, Muhammad Nouman (My University, 2011)
The concept of Corporate Social Responsibility varies from place to place and it is keep changing with time. The phrase CSR became more in use since early 60’s, among other several important factors CSR is based on, corporate governance and ethics Environmental stewardship, Sustainable development factors etc. According to researchers CSR based on Philanthropic, Economic and Legal ethics pillars. In Theoretical part of this study there is brief discussion on how SME’s operating in two different regions of world. One main purpose of this thesis is to understand the concept of CSR by studying different models and approaches. The data has been gathered using Interview method, Annual reports and Study of CSR reports of the case companies, to find out how these companies defining, practicing and implementing CSR. Conclusion shows that how these business entrepreneurs are focusing Defining, Practicing and Implementing on these factors and the parameters of CSR are accordance with their own understanding.
Keywords: Corporate Social Responsibility; Environmental Stewardship; Sustainable development; fi=Master's Degree Programme in Industrial Management|